GAMBARAN WORK-LIFE BALANCE PADA MOMPRENEUR - Brigitta Prasartika; Andhika Alexander Repi (Universitas Katolik Widya Mandala Surabaya, 2021)
Nowadays married women who do not work nine-to-five and choose to become housewives can be productive by generating high-achieving and income-generating works, one of which is by opening a business at home. Housewives who open businesses at home are commonly referred to as mompreneurs. However, being a mompreneur is not easy. A mompreneur needs to strive for a balance between her work life and also her personal life to maintain the sustainability of her business and her family. This study aims to observe how the work-life balance of the mompreneur is depicted, where work-life balance is an individual effort to balance work life and personal life. This research was conducted using qualitative phenomenological methods that applied the theory-led thematic analysis technique. The informants of this study are mompreneurs, who have been managing a business in the house which is operated online or offline with the business age is <2 years, and have or are currently nurturing a child <18 years old. Informants were selected using purposive and snowball techniques. The results of this study illustrate that the two informants show that there are three aspects of work-life balance, namely time balance, involvement balance, and satisfaction balance. Additionally, this study also found a new aspect of work-life balance, namely emotional balance, and the factors that affect the work-life balance of the two informants are the characteristics of the informant's trait or attitude, continuous learning, social support, and work overload.